2006
DOI: 10.1590/s0104-66322006000400002
|View full text |Cite
|
Sign up to set email alerts
|

Production of red pigments by Monascus ruber in culture media containing corn steep liquor

Abstract: -The production of red pigments by Monascus ruber was evaluated utilizing complex culture media composed of glucose or sucrose (10 g/L), corn steep liquor (5 or 10 g/L) and monosodium glutamate (0, 5.0, 7.6, 11.4 or 15.2 g/L). Medium containing 10 g/L glucose, 5 g/L corn steep liquor and 7.6 g/L monosodium glutamate resulted the highest values of extracellular red pigment absorbance (20.7 U) and productivity (0.35 U/h). This medium also produced better results than using semi-synthetic medium with analytical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 14 publications
(12 reference statements)
2
32
0
Order By: Relevance
“…The use of corn cob powder as a substrate for production of pigments by M. purpureus resulted in greater pigment production [68] than other substrates, as jackfruit seed [69], corn steep liquor [70], and grape waste [71]. In the black yeast Hortaea werneckii, it was observed that rice bran acts as the cheapest source for increased production of melanin by than wheat bran and coconut cake [72].…”
Section: Melaninmentioning
confidence: 99%
“…The use of corn cob powder as a substrate for production of pigments by M. purpureus resulted in greater pigment production [68] than other substrates, as jackfruit seed [69], corn steep liquor [70], and grape waste [71]. In the black yeast Hortaea werneckii, it was observed that rice bran acts as the cheapest source for increased production of melanin by than wheat bran and coconut cake [72].…”
Section: Melaninmentioning
confidence: 99%
“…Fatty acids can be transformed by Monascus into methyl ketones, but cannot be utilized as the sole carbon source [76][77][78]. Different types of carbon source are used depending upon the Monascus species, as shown in Table 2 [79][80][81][82][83][84]. Co-product of biodiesel Pure M. ruber [83] Corn steep liquor 5-10 M. ruber [84] Effect of nitrogen source…”
Section: Effect Of Carbon Sourcementioning
confidence: 99%
“…Different types of carbon source are used depending upon the Monascus species, as shown in Table 2 [79][80][81][82][83][84]. Co-product of biodiesel Pure M. ruber [83] Corn steep liquor 5-10 M. ruber [84] Effect of nitrogen source…”
Section: Effect Of Carbon Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…Pigment production varies with cultivation conditions. These filamentous fungi or the pigments derived from them are mostly used as food colour in imitation crabmeat, soybean products, jellies, milk, ice cream, fish ketchup, rice wine, soyabean cheese and anka production (Hamano and Kilikian, 2006).…”
Section: Introductionmentioning
confidence: 99%